2010
DOI: 10.1111/j.1742-1241.2010.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of opiate use

Abstract: The interpretation of toxicological findings is critical for the thorough investigation of the use and abuse of psychoactive substances. A positive analytical result for a sample taken could usually result in criminal proceedings and a punitive outcome for the defendant whose sample was analysed. The detection of markers of illicit opiate misuse is important both in the management of substance misuse and in the postmortem identification of illicit opiate use. The aim of this study was to emphasise the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
0
28
0
1
Order By: Relevance
“…The tea bags usually contain approximately 1 g of plant material, usually dried raw coca leaves that are also a natural source of cocaine. Urinary samples were collected at 2,5,8,15,21,24,43, and 68 hours after drinking the tea. When the tea was prepared, 1 cup of Peruvian coca tea had an average of 4.14 mg of cocaine, whereas 1 cup of Bolivian tea had an average of 4.29 mg of cocaine.…”
Section: Various Factors That Produce a Positive Cocaine Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tea bags usually contain approximately 1 g of plant material, usually dried raw coca leaves that are also a natural source of cocaine. Urinary samples were collected at 2,5,8,15,21,24,43, and 68 hours after drinking the tea. When the tea was prepared, 1 cup of Peruvian coca tea had an average of 4.14 mg of cocaine, whereas 1 cup of Bolivian tea had an average of 4.29 mg of cocaine.…”
Section: Various Factors That Produce a Positive Cocaine Resultsmentioning
confidence: 99%
“…Stefanidou et al reported that a morphine -tocodeine ratio in blood exceeding 1 is strong evidence that the person had abused heroin as opposed to taking a prescription medication containing codeine (21) . However, the illicit use of heroin also results in confi rmation of morphine in urine because heroin is fi rst metabolized to 6 -monoacetyl morphine and then into morphine, whereas the marker compound 6 -monoacetyl morphine may not be confi rmed in the urine of an illicit user of heroin because this compound can be detected only for a short time in heroin after heroin abuse.…”
Section: True-positive Opiate Tests Due To Use Of Medications and Ingmentioning
confidence: 99%
“…[1,2] Heroin itself is rarely found in urine or other body fluids, and is mainly excreted in the urine as free and conjugated morphine. [3,4] In addition, since illicit heroin contains acetylcodeine, codeine may also occur in urine after heroin intake. [3,4] In addition, since illicit heroin contains acetylcodeine, codeine may also occur in urine after heroin intake.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] In addition, since illicit heroin contains acetylcodeine, codeine may also occur in urine after heroin intake. [4,7] Morphine and codeine undergoes glucuronidation as major metabolic pathways leading to formation and excretion in urine of morphine-3-glucuronide (M3G), morphine-6glucuronide (M6G), codeine-6-glucuronide (CG) by action of UDP glucuronyltransferase (UGT) [1] , especially the UGT2B7 [8,9] and the UGT2B1 isoforms. [4,7] Morphine and codeine undergoes glucuronidation as major metabolic pathways leading to formation and excretion in urine of morphine-3-glucuronide (M3G), morphine-6glucuronide (M6G), codeine-6-glucuronide (CG) by action of UDP glucuronyltransferase (UGT) [1] , especially the UGT2B7 [8,9] and the UGT2B1 isoforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation